Komposisi sektoral dan pertumbuhan ekonomi: Dampaknya terhadap tingkat kemiskinan perdesaan di 34 Provinsi Indonesia - Ivani, Wardha Tia; Auwalin, Ilmiawan (Nur Science Institute, 2024)
This study aims to analyze the effect of economic growth based on sectoral composition on the rural poverty rate of 34 provinces in Indonesia in the 2011-2020 period. The method used is panel data regression because the data combines 2011-2020 time series data and cross-sectional data from 34 provinces in Indonesia using the REM model (Random Effect Model). The variables used in this study are the GRDP rate of the agricultural sector, the GRDP rate of the non-agricultural sector, the average length of schooling, the open unemployment rate, and village funds on the level of rural poverty in Indonesia. The results showed that simultaneously, all independent variables had a significant effect on the level of rural poverty in Indonesia, and partially, the agricultural sector GDP rate, average length of schooling, and open unemployment rate significantly reduced poverty. However, the GRDP rate variable in the non-agricultural sector and village funds has no significant effect on reducing poverty.